Complex permeability, permittivity and microwave absorption properties of barium hexaferrite synthesized from natural iron sand. Issue 1 (April 2021) - Handoko, E; Sugihartono, I; Marpaung, M A; Budi, S; Fahdiran, R; Randa, M; Jalil, Z; Alaydrus, M
Abstract: In this paper, the barium hexaferrite was successfully prepared by a conventional ceramic method and the precursors of BaCO3 and natural iron sand from Puger Beach, Jawa Timur-Indonesia. To develop a microwave absorbing material, the complex permeability, permittivity, and microwave absorption ability were investigated using a vector network analyzer (VNA) in the frequency range of 8.2-12.4 GHz. The results showed that barium hexaferrite presented an excellent broadband absorption (>90%, RL <-10dB) and a suitable absorber with high broad bandwidth and attenuation in the microwave frequency range.